Transcatheter aortic valve‐in‐valve‐in‐valve implantation with three‐dimensional printing guidance: A case report. Issue 7 (5th May 2020) - Basman, Craig; Seetharam, Karthik; Pirelli, Luigi; Kliger, Chad A.
Abstract: Background: Valve‐in‐valve implantation (ViV) has become a valid option for the treatment of bioprosthetic valve failure. We describe the first in‐man transfemoral transcatheter aortic valve replacement (TAVR) or "turducken" in a patient with previous TAVR within surgical aortic valve replacement with preprocedural guidance utilizing three‐dimensional (3D) printing and intraprocedural guidance with fusion imaging. Case Summary: A 65‐year‐old male with a previous valve‐in‐valve with a transcatheter Melody valve presented with symptomatic severe valvular and paravalvular aortic incompetence. Using 3D printing for preprocedural guidance and computed tomography angiography‐fluoroscopy fusion imaging for intraprocedural guidance we successfully placed a 29 mm self‐expanding valve with minimal residual gradients. The patient continued to be asymptomatic at 1‐ and 5‐year follow‐up. Discussion: We describe the first in man aortic valve‐in‐valve‐in‐valve using preprocedural guidance with 3D printing and intraprocedural guidance with fusion imaging. The valve has continued to demonstrate good function up to 5 years postprocedure suggesting that transcatheter aortic valve‐in‐valve‐in‐valve may be feasible with the proper pre‐ and intraprocedural guidance.